2013
DOI: 10.1097/mop.0b013e32835ad208
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament prevention strategies

Abstract: Early specialization and increased demand for peak performance at a time of major physiological change, lack of physical fitness and neuromuscular deficits have contributed to an increase in ACL injuries in young athletes. Various preventive training programmes have been developed, but their effectiveness is debatable. We encourage young athletes to partake in preseason training programmes focused on strengthening, neuromuscular and proprioceptive training units under the appropriate supervision of qualified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Multiple randomized controlled trials over the last two decades have demonstrated that ACL injury prevention through regular neuromuscular agility training programs is highly successful in the adolescent population [42,43,44,45]. Essential components of prevention programs in children and adolescents include strengthening, plyometric and balance training, and neuromuscular training with feedback to modify technique [46]. This may artificially induce the neuromuscular spurt and have the potential to reduce the risk of ACL injury in young athletes [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple randomized controlled trials over the last two decades have demonstrated that ACL injury prevention through regular neuromuscular agility training programs is highly successful in the adolescent population [42,43,44,45]. Essential components of prevention programs in children and adolescents include strengthening, plyometric and balance training, and neuromuscular training with feedback to modify technique [46]. This may artificially induce the neuromuscular spurt and have the potential to reduce the risk of ACL injury in young athletes [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Essential components of prevention programs in children and adolescents include strengthening, plyometric and balance training, and neuromuscular training with feedback to modify technique [46]. This may artificially induce the neuromuscular spurt and have the potential to reduce the risk of ACL injury in young athletes [46,47]. It is therefore recommended that young athletes be encouraged to partake in preseason training programs focused on strengthening, neuromuscular, and proprioceptive training, under the appropriate supervision of qualified personnel [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 8 studies met inclusion criteria and of these, only three ACL intervention programs (Sportsmetrics, Prevent Injury and Enhance Performance, and Knee Injury Prevention) successfully reduced noncontact ACL injury incidence rates in female adolescent athletes. Ladenhauf et al [109] recommend that young athletes should be encouraged to partake in preseason training programs focused on strengthening, neuromuscular and proprioceptive training units under the appropriate supervision of qualified personnel [109]. …”
Section: Injury Preventionmentioning
confidence: 99%
“…9,10,18 A recent review of injury prevention programs in youth athletes concluded that the benefit of preventive exercises in children remains unknown. 30 …”
mentioning
confidence: 99%